Dead or Alive? Factors Affecting the Survival of Victims during Attacks by Saltwater Crocodiles (Crocodylus porosus) in Australia - Fukuda, Yusuke; Manolis, Charlie; Saalfeld, Keith; Zuur, Alain (PLOS ONE, 2015)
Conflicts between humans and crocodilians are a widespread conservation challenge and the number of crocodile attacks is increasing worldwide. We identified the factors that most effectively decide whether a victim is injured or killed in a crocodile attack by fitting generalized linear models to a 42-year dataset of 87 attacks (27 fatal and 60 non-fatal) by saltwater crocodiles (Crocodylus porosus) in Australia. The models showed that the most influential factors were the difference in body mass between crocodile and victim, and the position of victim in relation to the water at the time of an attack. In-water position (for diving, swimming, and wading) had a higher risk than on-water (boating) or on-land (fishing, and hunting near the water's edge) positions. In the in-water position a 75 kg person would have a relatively high probability of survival (0.81) if attacked by a 300 cm crocodile, but the probability becomes much lower (0.17) with a 400 cm crocodile. If attacked by a crocodile larger than 450 cm, the survival probability would be extremely low (<0.05) regardless of the victim’s size. These results indicate that the main cause of death during a crocodile attack is drowning and larger crocodiles can drag a victim more easily into deeper water. A higher risk associated with a larger crocodile in relation to victim’s size is highlighted by children’s vulnerability to fatal attacks. Since the first recently recorded fatal attack involving a child in 2006, six out of nine fatal attacks (66.7%) involved children, and the average body size of crocodiles responsible for these fatal attacks was considerably smaller (384 cm, 223 kg) than that of crocodiles that killed adults (450 cm, 324 kg) during the same period (2006–2014). These results suggest that culling programs targeting larger crocodiles may not be an effective management option to improve safety for children.